Prevalence and unique patterns of lower limb hypermobility in elite ballet dancers - Phan, K.; Nicholson, L. L.; Hiller, C. E.; Chan, C. (Physical Therapy in Sport, 2020)
Professional dancers exhibit greater hypermobility than pre-professional dancers at the hip, subtalar and midfoot joints. Hypermobility profiles reveals how dancers may achieve dance positions, eg. turn-out if lacking mobility at the hip. These hypermobility profiles may assist educators and clinicians in implementation of preventative or management strategies.